ANALISIS PENERAPAN PENDIDIKAN KARAKTER OLEH GURU SOSIOLOGI PADA SISWA KELAS X - Rusidi, Rusidi; Rustiyarso, Rustiyarso; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe general problem in this research is how analysis of the application of character education by sociology teacher to students in class x of SMAN 2 sungai raya. In this research the method used  is descriptive method with qualitative research form. Data collection techniques used are direct observation techniques, direct communication techniques and documentary study techniques, while the data collection tools used are observation, interviews, and documentation. From the results of the research it can be concluded that the analysis of the application of character education by sociology teacher to student in class x it is good enough. This can be seen from the application of religious values carried out by the teacher by guiding and directing students to carry out the routine of reading the scripture according to the beliefs held, and the application of tolerance values conducted by teacher to teach students to be more respectful of teachers and fellow students, As well as the application of disciplinary values to discipline students firmly, teachers do this in providing learning such as providing motivation, advice, direction, and strict sanctions so that students have good behavior. With the implementation of the values of character education carried out by teacher towards students, it is very influential and simultaneously determines the success of education that exists in schools.  Keyword: Application of Character Education, Sociology TeacherAbstractThe general problem in this research is how analysis of the application of character education by sociology teacher to students in class x of SMAN 2 sungai raya. In this research the method used  is descriptive method with qualitative research form. Data collection techniques used are direct observation techniques, direct communication techniques and documentary study techniques, while the data collection tools used are observation, interviews, and documentation. From the results of the research it can be concluded that the analysis of the application of character education by sociology teacher to student in class x it is good enough. This can be seen from the application of religious values carried out by the teacher by guiding and directing students to carry out the routine of reading the scripture according to the beliefs held, and the application of tolerance values conducted by teacher to teach students to be more respectful of teachers and fellow students, As well as the application of disciplinary values to discipline students firmly, teachers do this in providing learning such as providing motivation, advice, direction, and strict sanctions so that students have good behavior. With the implementation of the values of character education carried out by teacher towards students, it is very influential and simultaneously determines the success of education that exists in schools.  Keyword: Application of Character Education, Sociology Teacher